Enough chit‐chat, strike! Deliberation and agonism in corporate governance. Issue 1 (6th September 2022) - Richard, Stanislas
Abstract: This conceptual paper contributes to the critique of a body of literature that will be named 'deliberative corporate governance' by defending non‐deliberative acts performed by stakeholders. It first argues that this literature introduces to the corporation a decision‐making process where it does not belong, given the corporation's economic role. This leads to an 'efficiency constraint' on any attempt to justify deliberation – deliberative governance theorists must show that it is the most efficient and cost‐effective way to address the issues that concern them. A real case example where deliberation would have been counter‐productive in that regard will show that this is not the case. Building on this example, the paper uses the theory of democratic agonism to argue that non‐deliberative acts should be part of governance. A sketch of managerial duties vis‐à‐vis such acts is attempted as well. The paper does not seek to reject deliberative corporate governance entirely, but rather to defend the importance of non‐deliberative practices in addressing its theoretical concern. It makes a conceptual contribution to corporate governance theory, from which it draws practical implications for stakeholders‐oriented management.